Separation of metals and phosphorus from incinerated sewage sludge ash - Ito, A (Water science and technology : a journal of the International Association on Water Pollution Research, 2013)
Microbial acidification of incinerated sewage sludge ash and dissolution of metals from the acidified ash were investigated using a semi-batch reactor at different solid retention times (SRTs). The average pH values ranged from 0.91 to 1.2 at SRTs longer than 10 days, whereas the reduction of SRT to 4 days resulted in an increase in the pH value to about 2. The dissolution efficiencies of Al, As, Cd, Cu and Mn were greater than 60% at a SRT of 4 days. Moreover, the effect of pH on precipitation of metals and P (dissolution of 80%) in the filtrate removed from the acidified sewage ash suspension, and the separation of phosphorus and the other metals in the filtrate using ethylenediaminetetraacetic acid (EDTA) or ferric ion, were examined. Although neutralisation of the filtrate to a pH of 5 simultaneously precipitated 100% of Al and 80% of P recovered from the acidified sewage ash, the addition of EDTA decreased their precipitation to 70 and 50%, respectively, at the same pH value, which would promote precipitation of P as calcium phosphate. Furthermore, neutralising to a pH of 2.5 after the addition of ferric ion precipitated P separately from Al and heavy metals